Visualization of real-time receptor endocytosis in dopamine neurons enabled by NTSR1-Venus knock-in mice - Ehrlich, Aliza T.; Couvineau, Pierre; Schamiloglu, Selin; Wojcik, Stefan; Da Fonte, Dillon; Mezni, Amina; von Zastrow, Mark; Bender, Kevin J.; Bouvier, Michel; Kieffer, Brigitte L. (Frontiers in Cellular Neuroscience, 2022)
Dopamine (DA) neurons are primarily concentrated in substantia nigra (SN) and ventral tegmental area (VTA). A subset of these neurons expresses the neurotensin receptor NTSR1 and its putative ligand neurotensin (Nts). NTSR1, a G protein-coupled receptor (GPCR), which classically activates Gαq/calcium signaling, is a potential route for modulating DA activity. Drug development efforts have been hampered by the receptor’s complex pharmacology and a lack of understanding about its endogenous location and signaling responses. Therefore, we have generated NTSR1-Venus knock-in (KI) mice to study NTSR1 receptors in their physiological context. In primary hippocampal neurons, we show that these animals express functional receptors that respond to agonists by increasing intracellular calcium release and trafficking to endosomes. Moreover, systemic agonist administration attenuates locomotion in KIs as it does in control animals. Mapping receptor protein expression at regional and cellular levels, located NTSR1-Venus on the soma and dendrites of dopaminergic SN/VTA neurons. Direct monitoring of receptor endocytosis, as a proxy for activation, enabled profiling of NTSR1 agonists in neurons, as well as acute SN/VTA containing brain slices. Taken together, NTSR1-Venus animals express traceable receptors that will improve understanding of NTSR1 and DA activities and more broadly how GPCRs act in vivo.